The Influence of Brand Image, Customer Value, and Product Quality on Customer Satisfaction - Wibowo, Wuryanto; Pujiati, Herni (Dinasti Publisher, 2025)
This study aims to determine the effect of brand image, customer value, and product quality on customer satisfaction (study of coffee shop customers at Forestthree Coffee Transyogi). The number of respondents is 80 respondents. The results showed that there is a brand image that does not have a positive and significant effect on customer satisfaction. This can be seen from the t-count value of 0.587 < t table of 1.992 and the sig value of Brand Image (X1) of 0.218> 0.05. So it can be concluded that H0 is accepted and Ha is rejected, and for customer value, product quality has a positive influence on customer satisfaction. This can be seen from the t-count value of 7.362 (X2), 5.782 (X3) > t table of 1.992. The results of the tests that have been carried out also show that customer value and product quality simultaneously have an influence on customer satisfaction as evidenced by a significant value of 0.000 < 0.05 and F count 122,550 > F table 2.73. For the DW value is 1.738, based on this, it is obtained that the value of dL = 1.560, the value of dU = 1.715, the value of 4-dL = 2.440, and the value of 4-dU = 2.285. Therefore, it can be concluded that there is no auto-correlation in the linear regression model because the value of dU(1.715) < DW (1.738) < 4-dU (2.285). The conclusion of this study is that customer satisfaction is caused by customer value and product quality. As for Customer Satisfaction does not happen which is caused by the Brand Image. Suggestions for this researcher are then expected to look for research materials that have an impact or have a positive effect on each of the variables.